SENI KARAWITAN YANG MANDIRI - Ening Sekarningsih (LP2M ISBI Bandung, 2015)
Sundanese Karawitan is currently experiencing stagnation resulting from the foreign cultural influences thereby impacting the continuity of Karawitan itself. Various attempts of preservation, fostering, and development for Karawitan have continuously and sustainably been done by individuals, communities, and institutions for the sake of the continuity and eternity of the art. One of Karawitan arts needs to be preserved is Karawitan Mandiri that comes from people for people